Administration of Melatonin in Diabetic Retinopathy Is Effective and Improves the Efficacy of Mesenchymal Stem Cell Treatment - Samraa H. Abdel-Kawi; Khalid S. Hashem (Stem Cells International)
Stem cell transplantation is a promising therapeutic technique for the treatment of a variety of diseases; nevertheless, stem cell therapy may not always work as well as it could. The goal of this study was to test the hypothesis that employing a powerful antioxidant like melatonin improves stem cell transplantation success and potentiates stem cell function in the therapy of diabetic retinopathy. For this purpose, 50 adult male rats were divided into the following: control group: this group received 0.5 ml of 0.1 M of sodium citrate buffer (pH=4.5) (intraperitoneal (I.P.)). The confirmed diabetic rats were divided into 4 groups: diabetic group: confirmed diabetic rats received no treatments with a regular follow of the blood glucose profile for 8 weeks; melatonin group: confirmed diabetic rats received melatonin (5 mg/kg/day); stem cell group: the confirmed diabetic rats were given intravitreal injection of stem cells (2 μl cell suspension of stem cells (3×104 cells/μl)); and melatonin+stem cell group: confirmed diabetic rats received melatonin (5 mg/kg/day), orally once daily for 8 weeks, and 2 μl cell suspension of stem cells (3×104 cells/μl) was carefully injected into the vitreous cavity. Our results showed that administration of melatonin and/or stem cell restored the retinal oxidative/antioxidant redox and reduced retinal inflammatory mediators. Coadministration of melatonin and stem cells enhanced the number of transplanted stem cells in the retinal tissue and significantly reduced retinal BDEF, VEGF, APOA1, and RBP4 levels as compared to melatonin and/or stem alone. We may conclude that rats treated with melatonin and stem cells had their retinal oxidative/antioxidant redox values restored to normal and their histological abnormalities reduced. These findings support the hypothesis that interactions with the BDEF, VEGF, APOA1, and RBP4 signaling pathways are responsible for these effects.